2022
DOI: 10.1093/eurheartj/ehac544.072
|View full text |Cite
|
Sign up to set email alerts
|

Global longitudinal strain improvement after iron replacement in stable heart failure patients – FER-Strain study

Abstract: Background Iron deficiency in patients with heart failure with reduced left ventricular ejection fraction (LVEF) confers a poor prognosis in terms of hospital admissions and mortality, worsening functional class and quality of life. Its replacement with ferric carboxymaltose (FCM) has demonstrated to improve clinical parameters, however, the way it is achieved remains unclear. Improvement of myocardial contractility is proposed as possible hypothesis and global longitudinal strain (GLS) could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
2
0
1
Order By: Relevance
“…Whereas these previous studies in populations with unknown or low rate of optimal medical treatment for HFrEF noted early improvements in LVEF after iron treatment, [29][30][31] in our study we observed no significant change in LVEF but an early improved LV-GLS, thus suggesting that iron repletion leads to an incipient increase in contractility that is detected by LV-GLS before an eventual improvement of the LVEF. It is possible that the high rate of recommended treatment for HF in our patients (according to the 2016 Guidelines 20 ) would have resulted in an optimized LVEF, consequently not initially so influenceable by the effect of iron repletion.…”
Section: Effects Of Iron Deficiency and Intravenous Iron Treatment On...contrasting
confidence: 98%
See 2 more Smart Citations
“…Whereas these previous studies in populations with unknown or low rate of optimal medical treatment for HFrEF noted early improvements in LVEF after iron treatment, [29][30][31] in our study we observed no significant change in LVEF but an early improved LV-GLS, thus suggesting that iron repletion leads to an incipient increase in contractility that is detected by LV-GLS before an eventual improvement of the LVEF. It is possible that the high rate of recommended treatment for HF in our patients (according to the 2016 Guidelines 20 ) would have resulted in an optimized LVEF, consequently not initially so influenceable by the effect of iron repletion.…”
Section: Effects Of Iron Deficiency and Intravenous Iron Treatment On...contrasting
confidence: 98%
“…Another study methodologically similar to ours, 31 in iron‐deficient non‐anemic patients with LVEF < 50% detected on echocardiography a significant improvement of LVEF (2.5%) and GLS (−1.1%) after 4 weeks of ferric carboxymaltose. Despite some differences with our study, such as the LVEF threshold to include patients, or the lack of data on baseline medical treatment, in both studies an improvement in GLS was detected 4 weeks after treatment.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation